IDENTIFIKASI PENERAPAN SANITASI PADA LINGKUP PERALATAN PRODUKSI KERIPIK SINGKONG (Manihot uttilisima) BERDASARKAN CRITICAL POINT (Studi Kasus di Industri GNP Snack, Muntilan, Magelang, Jawa Tengah) - , RIMA NURUL ARIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Production of cassava chips have not been accompanied by improved sanitation. Cassava chips potentially dangerous, requiring the handling and application of hygiene program. Handling hazards and application programs can be carried out with due regard to hygiene sanitation equipment, the availability of the next process to reduce or eliminate potential hazards, sanitation workers and pay attention to the effect of the process on the creation of products that suit the criteria of producers and consumers. Therefore, immediate action is necessary for the application of sanitary and determination of the critical point by identifying potential hazards so that potential hazards can be minimized. The data identified for the application of sanitary and determination of the critical point includes sanitation equipment, potential hazards, process parameters, material handling, availability of the next process to reduce or eliminate the potential hazard, the effect of the creation process and product criteria sanitation workers in each production process cassava chips. From these data, further identified and analyzed so that it will be found stage of the process as a critical point of the worst. Identify the application of sanitary equipment based on the critical point for each stage in the process industry GNP Snack with the highest critical point is at the frying stage. The critical point is due to the equipment and the sanitation workers less than the maximum, the unavailability of the next process to reduce or eliminate potential hazards such as hydrogen cyanide, rust, flavor and saturated fatty acids. In addition, the frying stage is the stage of deciding the formation of products of cassava chips.